The effects of IFITM1 and IFITM3 gene deletion on IFNγ stimulated protein synthesis - Gómez-Herranz, Maria; Nekulova, Marta; Faktor, Jakub; Hernychova, Lenka; Kote, Sachin; Sinclair, Elizabeth H; Nenutil, Rudolf; Vojtesek, Borivoj; Ball, Kathryn L; Hupp, Ted R (Cellular signalling, 2019)
Interferon-induced transmembrane proteins IFITM1 and IFITM3 (IFITM1/3) play a role in both RNA viral restriction and in human cancer progression. Using immunohistochemical staining of FFPE tissue, we identified subgroups of cervical cancer patients where IFITM1/3 protein expression is inversely related to metastasis. Guide RNA-CAS9 methods were used to develop an isogenic IFITM1/IFITM3 double null cervical cancer model in order to define dominant pathways triggered by presence or absence of IFITM1/3 signalling. A pulse SILAC methodology identified IRF1, HLA-B, and ISG15 as the most dominating IFNγ inducible proteins whose synthesis was attenuated in the IFITM1/IFITM3 double-null cells. Conversely, SWATH-IP mass spectrometry of ectopically expressed SBP-tagged IFITM1 identified ISG15 and HLA-B as dominant co-associated proteins. ISG15ylation was attenuated in IFNγ treated IFITM1/IFITM3 double-null cells. Proximity ligation assays indicated that HLA-B can interact with IFITM1/3 proteins in parental SiHa cells. Cell surface expression of HLA-B was attenuated in IFNγ treated IFITM1/IFITM3 double-null cells. SWATH-MS proteomic screens in cells treated with IFITM1-targeted siRNA cells resulted in the attenuation of an interferon regulated protein subpopulation including MHC Class I molecules as well as IFITM3, STAT1, B2M, and ISG15. These data have implications for the function of IFITM1/3 in mediating IFNγ stimulated protein synthesis including ISG15ylation and MHC Class I production in cancer cells. The data together suggest that pro-metastatic growth associated with IFITM1/3 negative cervical cancers relates to attenuated expression of MHC Class I molecules that would support tumor immune escape.
Keywords: MHC antigeny I. třídy; Cell Line; Membrane Proteins; RNA-Binding Proteins; proteiny vázající RNA; Humans; Uterine Cervical Neoplasms; lidé; Female; buněčné linie; proteosyntéza; Histocompatibility Antigens Class I; nádory děložního čípku; Antigens, Differentiation; membránové proteiny; ženské pohlaví; Protein Biosynthesis; diferenciační antigeny